Functional Role of Natural Antioxidants in Controlling Oxidative Stress Associated with SARS-CoV-2 Infection - Parasuraman, Subramani; Vedam, Venkata Kanthi V.; Uppugunduri, Chakradhara Rao S. (Coronaviruses, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a pathogenic coronavirus that emerged in late 2019, resulting in coronavirus disease (COVID-19). COVID-19 can be potentially fatal among a certain group of patients. Older age and underlying medical illness are the major risk factors for COVID-19-related fatal respiratory dysfunction. The reason for the pathogenicity of COVID-19 in the older age group remains unclear. Factors, such as coagulopathy, cytokine storm, metabolic disruption, and impaired T cell function, may worsen the symptoms of the disease. Recent literature has indicated that viral infections are particularly associated with a high degree of oxidative stress and an imbalance of antioxidant response. Although pharmacological management has taken its place in reducing the severity of COVID-19, the antioxidants can serve as an adjunct therapy to protect an individual from oxidative damage triggered by SARS-CoV-2 infection. In general, antioxidant enzymes counteract free radicals and prevent their formation. The exact functional role of antioxidant supplements in reducing disease symptoms of SARS-CoV-2 infection remains mostly unknown. In this review, the functional role of natural antioxidants in SARS-CoV-2 infection management is discussed in brief.
Keywords: xanthine oxidase